I robot di Karel Čapek: 100 anni di metamorfosi. I testi dell'autore su "R.U.R." e i documenti della ricezione italiana negli anni Venti e Trenta - Alessandro Catalano (eSamizdat)
This study clarifies the events that led to the appearance of the word 'robot' in world culture and shows the international reception of the work of Karel Čapek R.U.R. (Rossum's Universal Robots), which caused a deep transformation of the robot into a mechanical anthropomorphic creature. All the author's texts dedicated to the topic are translated into Italian for the first time, and primary sources which testify the resonance that R.U.R. received in Italy have been republished.